Eradication of HCV Infection with the Direct-Acting Antiviral Therapy in Renal Allograft Recipients - Armando, Calogero (Biomed Res Int, 2019)
Hepatitis C virus (HCV) infection unfavorably affects the survival of both renal patients undergoing hemodialysis and renal transplant recipients. In this subset of patients, the effectiveness and safety of different combinations of interferon-free direct-acting antiviral agents (DAAs) have been analyzed in several small studies. Despite fragmentary, the available data demonstrate that DAA treatment is safe and effective in eradicating HCV infection, with a sustained virologic response (SVR) rates nearly 95% and without an increased risk of allograft rejection. This review article analyzes the results of most published studies on this topic to favor more in-depth knowledge of the readers on the subject. We suggest, however, perseverating in this update as the optimal DAA regimen may not be proposed yet, because of the expected arrival of newer DAAs and of the lack of data from large multicenter randomized controlled trials.